Gross efficiency during rowing is not affected by stroke rate - Hofmijster, M. J.; van Soest, A. J.; de Koning, J. J. (Medicine & Science in Sports & Exercise, 2009)
Purpose: It has been suggested that the optimal stroke rate in rowing is partly determined by the stroke-rate dependence of internal power losses. This should be reflected in a stroke-rate dependency of gross efficiency (egross). The purpose of this study was to investigate if egross is affected by stroke rate. A second aim was to determine whether internal power losses can be estimated by the negative power output during the stroke cycle (Pnegative).